PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA - Setiawan, Dicky Eka Kurnia; Basir, Udjang Pairin M.; Susilo, Claudya Zahrani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Role playing is one of the learning models that has not been widely used by teachers in providing understanding to students. There are still many teachers who use traditional learning models in their teaching. In this study, researcher aimed to measure the effect of role playing model to the student’s learning outcomes based on before students are given treatment and after treatment. This study uses a qualitative research technique with the type of library research. The source of this research resulted from several journal and also several theses. Researchers using the content analysis method in analyzing the data. The average student’s score of twelve articles and theses is 57. Then after being treated with a role playing learning model, the student’s average value from twelve articles and theses increases about 19% to 76. From these data it can be said that the role playing learning model can improve student learning outcomes.